Migration, AIDS, and urban food security in southern and eastern Africa: Case studies in Namibia, South Africa, and Ethiopia - Drimie, Scott (International Food Policy Research Institute, 2008)
Migration, AIDS epidemics, and urban food security, interact in complex ways that are little researched and understood in the Southern and Eastern African context. To date, research on urban food security has been concerned with urban systems of acquisition and production, with an emphasis on the informal sector and more recently on urban agriculture. Much less attention has been paid to linkages and food chains between rural and urban areas and the degree to which they are embedded within systems of migration.